Molecularly engineered graphene oxide anchored metal organic assembly: an active site economic bi-functional electrocatalyst - Jhajharia, Suman Kumari; Selvaraj, Kaliaperumal (FlatChem, 2021)
Low-temperature fuel cells are the most promising sustainable energy technology as they use hydrogen, an environmentally clean fuel. However, the sluggish kinetics of oxygen electrochemistry, a chronic issue, is holding them from commercialization. Herein, we address this issue through a molecular level design of a Graphene oxide anchored Metal Organic Molecular Assembly (G-MOMA) based catalyst. This non-precious metal catalyst consists of Ni and Fe ions ligated by graphene oxide supported terpyridine, a unique molecular assembly design that maximizes the utilization of active metal centers. This G-MOMA catalyst brings down an over potential (240 mV) for oxygen evolution reaction (OER) as close as that of the bench mark catalyst Ru/C with an impressive Tafel slope of 58 mV/dec and a cyclic stability of >30,000 cycles. G-MOMA excels in oxygen reduction reaction (ORR) too with an onset at 0.88 V (vs RHE). The remarkably stable G-MOMA catalyst surprises with an excellent bi-functionality towards both OER and ORR with an overall potential difference of mere 0.77 V, which is 180 mV and 70 mV lesser than the standard Pt/C and Ru/C catalysts, respectively. The G-MOMA catalyst is well in the activity range of the state-of-art bi-functional catalysts and yet cheaper by many folds.
Keywords: Bi-functional electrocatalyst; graphene oxide; Metal organic molecular assembly; Oxygen Evolution Reaction; oxygen reduction reaction; terpyridine